2022
DOI: 10.21037/atm-22-2756
|View full text |Cite
|
Sign up to set email alerts
|

The use of Esketamine in CT-guided percutaneous liver tumor ablation reduces the consumption of remifentanil: a randomized, controlled, double-blind trial

Abstract: Background: In the anesthesia management of percutaneous liver tumor ablation, the requirement of analgesia is very strict. Currently, intravenous anesthesia is commonly used, such as remifentanil combined with sedative drugs. However, the pain relief is not instantaneous after increasing the dosage of remifentanil.Esketamine, a medium-or long-term analgesic drug, does not inhibit respiration to maintain patient comfort during the ablation and reduces the consumption of remifentanil. Therefore, this experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 25 Su et al found that esketamine administration significantly decreased the dosage of remifentanil and reduced the incidence of severe pain with liver tumor ablation. 26 However, Brinck et al revealed that intraoperative S(+)-ketamine administration did not alleviate postoperative pain and oxycodone consumption undergoing major lumbar fusion surgery. 27 In the present study, our results indicated that low-dose esketamine infusion relieved NRS pain scores during the first postoperative 6 h period and high-dose esketamine alleviated NRS pain scores during the first postoperative 24 h period.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Su et al found that esketamine administration significantly decreased the dosage of remifentanil and reduced the incidence of severe pain with liver tumor ablation. 26 However, Brinck et al revealed that intraoperative S(+)-ketamine administration did not alleviate postoperative pain and oxycodone consumption undergoing major lumbar fusion surgery. 27 In the present study, our results indicated that low-dose esketamine infusion relieved NRS pain scores during the first postoperative 6 h period and high-dose esketamine alleviated NRS pain scores during the first postoperative 24 h period.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence indicates that the use of esketamine can reduce the dosages of remifentanil and propofol required for the maintenance of anesthesia. 2,3 Third, this study used a single-mode postoperative analgesia strategy in all patients, ie, non-steroidal antiinflammatory drugs were administered if the postoperative numeric rating scale pain score was more than 3. In fact, the current Enhanced Recovery After Surgery protocols recommend a multimodal strategy for postoperative analgesia, in which nerve or fascial plane block and a package of basic analgesics, such as paracetamol, non-steroidal antiinflammatory drugs or cyclooxygenase-2 specific inhibitors, and dexamethasone, is included.…”
Section: Dear Editormentioning
confidence: 99%
“…It has a stronger affinity for NMDA receptors but fewer side effects than ketamine, providing a more comfortable experience for patients 11 . Some clinical data have shown that S‐ketamine as a general anesthetic can be used safely and effectively in general anesthesia for many types of surgery at a dose of 0.5 mg/kg in clinical practice 12 . For pediatric surgery for lower limb fracture, S‐ketamine at dose of 0.5 mg/kg combined with the nerve block has a perfect analgesic effect, fast anesthetic effect, and low incidence of pediatric agitation 13 .…”
Section: Introductionmentioning
confidence: 99%
“… 11 Some clinical data have shown that S‐ketamine as a general anesthetic can be used safely and effectively in general anesthesia for many types of surgery at a dose of 0.5 mg/kg in clinical practice. 12 For pediatric surgery for lower limb fracture, S‐ketamine at dose of 0.5 mg/kg combined with the nerve block has a perfect analgesic effect, fast anesthetic effect, and low incidence of pediatric agitation. 13 This suggests that S‐ketamine does have a distinct advantage in the induction of general anesthesia.…”
Section: Introductionmentioning
confidence: 99%